Seed Germination and Seedling Growth Potential of Haricot Bean Under Laboratory Conditions - Alemu, Melkam Anteneh (International Journal For Research In Agricultural And Food Science, 2019)
Haricot bean (Phaseolus vulgaris L.) differ in their low temperature tolerance regarding growth and yield. Varieties tolerant to low temperature during germination and carriers of the seed quality standards are needed for the success of the crop. Ten seeds were placed per petridish uniformly and covered with lid to prevent loss of moisture through evaporation. The seeds were allowed to germinate for 10 days at room temperature. The germination percentage was recorded on the 10th day. Germination was considered to have occurred when radicles attained a length of 2 mm. The objectives of this study were to evaluate the germination of bean seedlings under controlled environment with in laboratory conditions. Trial were conducted with dry bean seed in moderate or controlled environment. The seedling, shoot length for varieties Awash-2 a little bit different than other two moreover seedling fresh and dry weights all are equal values. Morpho-agronomic data were used to evaluate the phenotypic performance of the different varieties before the seed or seedlings going on the field.